Despite available habitat at range edge, yellow‐cedar migration is punctuated with a past pulse tied to colder conditions. Issue 12 (12th September 2017) - Krapek, John; Hennon, Paul E.; D'Amore, David V.; Buma, Brian
Abstract: Aim: To explore the recent (past ~1, 000 year) migration history of yellow‐cedar ( Callitropsis nootkatensis ), a climate‐threatened tree, which appears to lag behind its potential climatic niche at a leading northern range edge, and infer its continued migration potential under changing climate. Location: Southeast Alaska, USA. Methods: We located 11 leading range edge yellow‐cedar stands near Juneau, Alaska, determined their proportional occupancy of modelled habitat and estimated stand ages to determine approximate time of establishment. We used future climate projections to determine the potential vulnerability of these leading edge populations using a well‐established risk factor for yellow‐cedar mortality in the region. Results: Despite abundant potential habitat, and having existed in the study area > 675 years, yellow‐cedar has only occupied a small proportion (<0.8%) of suitable habitat. Yellow‐cedar appears to have undergone a past pulse of successful regeneration and establishment during the Little Ice Age climate period, with little expansion in recent decades. Under high emissions future climate scenarios, nine of 11 stands (82%) may become exposed to climate conditions that predispose yellow‐cedar to root freezing injury by 2070. Main conclusions: We show that yellow‐cedar's migration near a northern range edge is episodic, with a past pulse of establishment during the Little Ice Age. When planning for the conservation and management of this culturally and economically valuable tree, forest managers should consider yellow‐cedar's currently limited migration at the leading edge, mortality emerging farther north in recent decades and potential vulnerability of range edge stands by 2070. The range of intense, climatic driven yellow‐cedar mortality is expanding northward and rapidly approaching the species' leading edge in southeast Alaska. Yellow‐cedar's episodic migration demonstrates that species may not respond linearly to a warming climate and that other factors controlling dispersal to suitable habitat must be considered for accurate range predictions.